Selected Decisions, 18th Edition (1993). (Selected Decisions, 1993)
This paper reports several IMF's selected decisions of the Executive Board and selected documents. The Executive Board approves the draft 'Guidelines for Determining the Amount of Reserve Assets to Be Paid in Connection with Subscriptions' set forth. These guidelines shall be considered by a Committee of the Executive Board established to consider an application for membership in the IMF or to consider a request for an increase in quota that is made outside the framework of a general review of quotas. A reasonable approximation of the amount of the subscription that has been paid in reserve assets in the past is the average of all reserve assets actually paid in terms of the quotas of all members, rather than the proportions paid in the past by individual members. In determining the amount of the reserve asset payment, account should also be taken of the effect the size of such payment would have on the remuneration that might be payable to the new member.